Improving Communication Across the Independent Living/Mental Health Divide - Baron, Richard C.; Dezenski, Linda; Rogers, Joseph (Disability Studies Quarterly, 2013)
Keywords: Centers for Independent Living, mental health, psychiatric disabilities, physical disabilities, inter-system collaboration Centers for Independent Living (CILs) increasingly recognize the importance of providing effective services and supports to individuals with psychiatric disabilities. While those with psychiatric disabilities turn to their local CIL for the same types of assistance as do others, serving people with psychiatric disabilities may suggest the need for CIL staff to communicate and/or collaborate with their local mental health (MH) authorities, mental health clinical and rehabilitation providers, and/or mental health peer-run service programs. Productive contact across the CIL / MH divide, however, is often difficult, reflecting both mutual unfamiliarity and long-standing tensions. CILs are often unsure how much their staff should know about mental illness (that is, about symptoms, diagnosis, medication, treatment, and rehabilitation alternatives), how closely they should work with traditional mental health treatment and rehabilitation providers, and how to connect to the expanding network of mental health peer-run services and supports. This article reviews these questions in the context of the tension between the mental health and independent living paradigms, and provides initial recommendations for improved communication and collaboration across the IL/MH divide.